Development of alkyl polyglucosides (APG) nanoemulsions containing ibuprofen as a delivery system for pharmaceutics / Nurul Shahidah Mohamad Shahripoddin - Nurul Shahidah , Mohamad Shahripoddin (2022)
Green, nonionic and biomimicking properties of alkyl polyglucosides (APGs) have contributed to the re-emergence of sugar-based surfactants recently. This research aims to investigate the influence of alkyl polyglucoside (APG) as a co-surfactant in nanoemulsion formulation containing ibuprofen, as a model drug, which is intended to be used for topical application. The phase behaviour of oil/surfactant/water system containing ibuprofen, stability properties and comparison of preliminary particle size were investigated. The results showed that the ternary phase diagram of the CrEL:APG12 system with a ratio of 9:1 has the largest transparent isotropic region. When comparing nanoemulsion formulations with and without APG, it showed that the system with APG exhibited higher emulsifying ability than CrEL surfactant alone which due to the APG co-surfactant could decrease the water affinity and increased the oil affinity of the systems. Several formulations with different surfactant mixtures (CrEL only, CrEL:APG08, CrEL:APG10, and CrEL:APG12) were prepared. The particle sizes ranged between 20-200 nm and polydispersity index of less than 0.25 were obtained. The cytotoxicity results of nanoemulsion with APG12 and nanoemulsion without APG12 showed no toxic effect against 3T3 cell line. Thus, APG co-surfactants prolonged the storage stability, improved the structural morphology, and enhanced ibuprofen permeation. This suggests that APG could be used as an alternative stabilizing agent and the formulated nanoemulsion system could be used as a drug carrier system for pharmaceutical applications.